Equity options during the shorting ban of 2008 - Nusret Cakici; Gautam Goswami; Sinan Tan (Journal of Risk and Financial Management, 2018)
The Securities and Exchange Commission's 2008 emergency order introduced a shorting ban of some 800 financials traded in the US. This paper provides an empirical analysis of the options market around the ban period. Using transaction level data from OPRA (The Options Price Reporting Authority), we study the options volume, spreads, pricing measures and option trade volume informativeness during the ban. We also consider the put-call parity relationship. While mostly statistically significant, economic magnitudes of our results suggest that the impact of the ban on the equity options market was likely not as dramatic as initially thought.
Keywords: 330; SEC; shorting ban; OPRA; intraday stock options